Sistem Pakar Mendiagnosa Penyakit Flu Babi Menerapkan Metode Hybrid Case Based - Ricki Avrizal (STMIK Budi Darma, 2019)
Expert system is an Artificial Intelligence program that combines the knowledge base with inference machines. This is a part of high-level specialization software, which seeks to duplicate the functions of an expert in a particular area of expertise. The expert system for diagnosing peanut plant disease aims to diagnose swine flu in humans, so that appropriate treatment can be carried out and does not cause outbreaks in the community. Swine flu is a disease that is very dangerous to humans, because it can cause death. For this disease, a very fast diagnosis is needed because it can be transmitted between humans to animals or vice versa and this disease can spread to an age group. Medical implementers, especially doctors, are still very limited when compared to the population that continues to increase. This makes people suffering from swine flu difficult to consult with doctors, as a result of this swine flu disease is increasingly widespread due to slow handling. Of these problems raises the idea of making an application that can diagnose swine flu disease and can help people affected by swine flu to get fast treatment. The methodology used in making this application is the Hybrid Case Based method. which is a combination of case based reasoning (CBR) with rule based reasoning (RBR). Basically CBR is one method that uses the previous case solution to solve a new case. While the RBR technique checks the input data based on the rules that have been stored in the rule base, both of which have their advantages and disadvantages.